Concomitant administration of a liquid formulation of human rotavirus vaccine (porcine circovirus-free) with routine childhood vaccines in infants in the United States: Results from a phase 3, randomized trial. Issue 10 (5th March 2021) - Abu-Elyazeed, Remon; Klein, Nicola P.; Moerman, Leentje; Povey, Michael; Pruitt, Anthony; Senders, Shelly; Silas, Peter; Bi, Dan; ,; Acevedo, Armando; Amisola, Rogelio; Anschutz, Luke; et al.
Highlights: A porcine circovirus-free human rotavirus vaccine (PCV-free HRV) has been developed. We compared routine vaccines coadministration with liquid PCV-free vs lyophilized HRV. We showed non-inferior immune responses for coadministration with PCV-free HRV vs HRV. We observe comparable safety profiles for liquid PCV-free HRV and lyophilized HRV. Liquid PCV-free HRV could be used as part of routine vaccination in United States. Abstract: Background: In response to the detection of porcine circovirus type 1 (PCV-1) in the human rotavirus vaccine (HRV), a PCV-free HRV (no detection of PCV-1 and PCV-2 according to the detection limit of tests used) was developed. Liquid (Liq) PCV-free HRV previously showed immunogenicity and safety profiles comparable to lyophilized (Lyo) HRV. Methods: This was a phase 3a, randomized, single-blind study (NCT03207750) conducted in the United States. Healthy infants aged 6–12 weeks received 2 doses (0, 2 months) of either Liq PCV-free HRV or Lyo HRV with routine vaccines (0, 2, 4 months): diphtheria-tetanus-acellular pertussis, hepatitis B and inactivated poliovirus combination vaccine (DTaP-HBV-IPV), monovalent tetanus toxoid-conjugated vaccine against Haemophilus influenzae type b (Hib-TT), and 13-valent pneumococcal conjugate vaccine. Co-primary objectives were: (i) to assess non-inferiority of immune responses to routine vaccine antigens 1 month post-dose 3 following co-administration with Liq PCV-free HRV compared to Lyo HRV; (ii) to rule out a 10% decrease in seroresponse to pertussis antigens after dose 3. Other objectives were to evaluate immunogenicity and safety of HRV vaccines. Results: Of 1272 vaccinated infants, 990 (489 in Liq PCV-free HRV and 501 in Lyo HRV group) were included in the per-protocol set. All statistical criteria were met, thus co-primary objectives were demonstrated. Seroprotection/seropositivity rates in both groups were high: 100% for diphtheria/tetanus, ≥99.3% for HBV, ≥99.8% for polio, ≥99.8% for each pertussis antigen, ≥90.8% for all pneumococcal serotypes except serotype 3 (≥69.1%), and ≥ 97.4% for Hib. Most infants seroconverted for anti-RV antibodies (76.3% of Liq PCV-free HRV and 78.9% of Lyo HRV recipients). Geometric mean concentrations/titers were comparable between groups. Incidences of adverse events and serious adverse events were similar between groups. Conclusion: Routine pediatric vaccines co-administered with Liq PCV-free HRV showed non-inferior immune responses and similar safety profiles to those following co-administration with Lyo HRV.